Municipal Solid Waste Management : Opportunities for Russia - International Finance Corporation (Washington, DC, 2017)
Municipal solid waste (MSW) management system is one of the key components of a country's overall environmental and resource efficiency framework. Inefficient MSW treatment in Russia today is causing negative environmental impact, and results in suboptimal use of raw materials and energy. If Russia optimized its MSW management policy and implemented modern technologies, by 2025 it could fully shift towards environmentally friendly MSW management system and recover up to 45 percent of waste. As a result, by 2025 more than 200 metric tons of MSW would be recovered to raw materials and energy instead of landfilling. This would require investing up to 40 billion and would generate additional 2 billion in revenues from recoverable fractions.